Polyurea microcapsules from isocyanatoethyl methacrylate copolymers. Issue 17 (17th May 2016) - Risangud, Nuttapol; Congdon, Thomas R.; Keddie, Daniel J.; Wilson, Paul; Kempe, Kristian; Haddleton, David M.
ABSTRACT: The synthesis of two types of isocyanate side chain containing copolymers, poly(methyl methacrylate‐ co ‐isocyanatoethyl methacrylate) (P(MMA‐ co ‐IEM)) and poly(benzyl methacrylate‐ co ‐isocyanatoethyl methacrylate) (P(BnMA‐ co ‐IEM)), which were synthesized by Cu(0)‐mediated radical polymerization, is reported. Polymerization proceeded to high conversion giving polymers of relatively narrow molar mass distributions. The incorporation of the bulky aromatic groups in the latter copolymer rendered it sufficiently stable toward hydrolysis and enabled the isolation of the product and its characterization by 1 H and 13 C NMR, and FTIR spectroscopy and SEC. Both P(MMA‐ co ‐IEM) and P(BnMA‐ co ‐IEM) were functionalized with dibutylamine, octylamine, and ( R )‐(+)‐α‐methylbenzyl‐amine, which further proved the successful incorporation of the isocyanate groups. Furthermore, P(BnMA‐ co ‐IEM) was used for the fabrication of liquid core microcapsules via oil‐in‐water interfacial polymerization with diethylenetriamine as crosslinker. The particles obtained were in the size range of 10–90 µm in diameter independent of the composition of copolymer. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2698–2705 Abstract : Poly(benzyl methacrylate‐ co ‐isocyanatoethyl methacrylate) (p(BnMA‐ co ‐IEM)) copolymers which are sufficiently stable toward hydrolysis were synthesized by Cu(0)‐mediated radical polymerization. The isocyanate side groups were exploited for postpolymerization modifications with different model amine compounds and for the fabrication of liquid core microcapsules via oil‐in‐water interfacial polymerization.